Justice Day - POPA, Nicolae (Journal of Legal Studies, 2015)
Each year, since 1993, Justice Day is celebrated at the beginning of July. And each year, the festivities are attended by representatives of the other powers, but this year no leaders of such powers honoured us with their presence. Each time, speeches are made to emphasise progress in the delivery of justice, while also addressing future prospects. This year was no different. Speeches talked about the nobleness of a judge‟s work, the advantages of implementing the new codes, the praises of European controllers and their encouragements on the line of "persuasive punishments". Emphasis was placed on the need to respect the independence of the judiciary, under conditions of attempts to infringe this principle coming from the legislature, the executive, the media, etc